Falsos cognados alemán-español que causan confusión en el aprendizaje del idioma alemán - Ramirez Mendoza, Sheyla Stephany (2019)
The present work entitled: "False German-Spanish cognates that cause confusion in the learning of the German language," has as main objective identify the false cognates of German and Spanish that cause confusion in the German language learning in the students of the secondary level’s second grade of “San Juan" school. When we study a language and learn its vocabulary, we realize that there are certain words that are very similar in writing or pronunciation to our mother tongue, but at the same time we are surprised that its meaning is totally different from ours. Which causes some confusion in the students' learning if we do not put emphasis on this situation and do not look for the necessary strategies to achieve an improvement in the teaching-learning process of the students. Therefore, we seek to know which false cognates that cause confusion in the learning of the German language in the second grade classroom are. In the same way, these words will serve as a reference for future researches related to the lexicon of a foreign language. This study was of descriptive character and had a sample of 23 students of the German course of the secondary level’s second grade of “San Juan" school, to whom an observation guide was applied, during a month and a half and also a test on false cognates with 19 items with the aim of collecting a set of words in German that cause greater confusion in the learning of the students. xi In sum, the results showed that the false cognates that cause the most confusion in the learning of the German language of the secondary level’s second grade students of “San Juan" school are: Art, Telefonieren, Mappe, Signature, Termin, Konkurrenz, Karte , Rat, Regal, Komisch, Rock and Vase, this is because students only see the signifier of the word but not the meaning, which causes the student to constantly make mistakes and this interferes with the correct learning of the cognates.